LOS DERECHOS HUMANOS Y SU RELACIÓN CON LA EXPULSIÓN DE EXTRANJEROS EN LA SEDE JUDICIAL DE AREQUIPA - Chonta Cabrera, Margarita Sugey (2020)
ABSTRACT The investigation is titled "Human Rights and their relationship with the Expulsion of Foreigners in the Judicial Headquarters of Arequipa" and the objective was to determine the relationship between human rights and the expulsion of foreigners in the judicial headquarters under study. This research is quantitative, basic, correlational, descriptive and of a non-experimental, transectional design. The population consisted of 25 lawyers, while the sampling was non-probabilistic, that is, for convenience and was made up of all lawyers. Finally, it was concluded that a direct and significant relationship was obtained with a p-value equal to 0.000 between the variable Human rights and Expulsion of foreigners. Keywords: Human rights, Expulsion of foreigners, Police detention, Use of police force